Differential divergence of three human pseudoautosomal genes and their mouse homologs: implications for sex chromosome evolution - Gianfrancesco, Fernando; Sanges, Remo; Esposito, Teresa; Tempesta, Sergio; Rao, Ercole; Rappold, Gudrun; Archidiacono, Nicoletta; Graves, Jennifer A. M.; Forabosco, Antonino; D'Urso, Michele (Genome research, 2001)
The human pseudoautosomal region 1 (PAR1) is essential for meiotic pairing and recombination, and its deletion causes male sterility. Comparative studies of human and mouse pseudoautosomal genes are valuable in charting the evolution of this interesting region, but have been limited by the paucity of genes conserved between the two species. We have cloned a novel human PAR1 gene, DHRSXY, encoding an oxidoreductase of the short-chain dehydrogenase/reductase family, and isolated a mouse ortholog Dhrsxy. We also searched for mouse homologs of recently reported PGPL and TRAMP genes that flank it within PAR1. We recovered a highly conserved mouse ortholog of PGPL by cross-hybridization, but found no mouse homolog of TRAMP. Like Csf2ra and Il3ra, both mouse homologs are autosomal; Pgpl on chromosome 5, andDhrsxy subtelomeric on chromosome 4. TRAMP, like the human genes within or near PAR1, is probably very divergent or absent in the mouse genome. We interpret the rapid divergence and loss of pseudoautosomal genes in terms of a model of selection for the concentration of repetitive recombinogenic sequences that predispose to high recombination and translocation. - [The sequence data described in this paper have been submitted to the EMBL data library under accession nos. AJ293620, AJ296079, and AJ293619.]